Role of an altered penicillin-binding protein in methicillin- and cephem-resistant Staphylococcus aureus. - Utsui, Y (1985)
About 80% of methicillin- and cefazolin-resistant strains of Staphylococcus aureus isolated clinically in Japan in 1982 retained their resistance even after elimination of penicillinase-encoding plasmids. The penicillin-binding proteins (PBPs) of the penicillinase-free, methicillin- and cephem-resistant subclones of Staphylococcus aureus (MRSA) were compared with those of spontaneous susceptible revertants which had been obtained by the replica method after 10 subcultures in drug-free media. A new PBP fraction (PBP2') having a molecular weight of 78,000 and low binding affinities for various beta-lactam antibiotics was found in MRSA exclusively. The levels of resistance of MRSA strains were reduced markedly by culturing them at 43 degrees C or at pH 5.2 or both. We found that the binding capacity of PBP2' for 14C-labeled penicillin G was decreased by preincubation of the membrane fractions of MRSA strains at 43 degrees C for 60 min and that the amount of PBP2' in MRSA strains grown at pH 5.2 was less than that the amount of PBP2' in MRSA strains grown at pH 7.0. Temperature- and pH-dependent expression of resistance in MRSA is likely to reflect the temperature sensitivity and neutral pH-dependent production of the specific PBP fraction (PBP2'). We suggest that MRSA strains can grow in the presence of beta-lactam antibiotics because of the low affinities of the specific PBP2' fraction for various beta-lactam antibiotics.